Lifetime Factors in Silicon 1980
DOI: 10.1520/stp35131s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Impurity-Decorated Stacking Faults on the Transient Response of Metal Oxide Semiconductor Capacitors

Abstract: The gettering effect of phosphorus diffusion to the back surface of a silicon wafer on oxidation-induced stacking faults has been studied by evaluating the generation lifetime from the transient response of metal oxide semiconductor (MOS) capacitors. The generation lifetime of wafers subjected to postoxidation phosphorus diffusion gettering is not remarkably decreased by the presence of stacking faults. On the other hand, the generation lifetime of waters subjected to preoxidation gettering is decreased by two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…279 Experimental data by Yasuteru Ichida and colleagues indicated that a POCl 3 gettering process introduced at the end of device fabrication was more successful than its introduction at the initiation of the device fabrication process. 287 HCl gettering, introduced by Rudolf Kreigler, DS&T Callinan 1979 Awardee, became an especially prevalent industrial technique. [288][289][290] 292 Gettering was initially believed to occur by formation of volatile metal chlorides, although the Gibbs free energy of formation of most metal chlorides was not negative.…”
Section: Gettering Methodologies (Nonoxygen Techniquesmentioning
confidence: 99%
“…279 Experimental data by Yasuteru Ichida and colleagues indicated that a POCl 3 gettering process introduced at the end of device fabrication was more successful than its introduction at the initiation of the device fabrication process. 287 HCl gettering, introduced by Rudolf Kreigler, DS&T Callinan 1979 Awardee, became an especially prevalent industrial technique. [288][289][290] 292 Gettering was initially believed to occur by formation of volatile metal chlorides, although the Gibbs free energy of formation of most metal chlorides was not negative.…”
Section: Gettering Methodologies (Nonoxygen Techniquesmentioning
confidence: 99%
“…10. The graph shows that the value of 1/tg is n~arly proportional to defect density d. Therefore, 1/tg can be expressed by 1/t~ ~-k " d + llto where k is the proportional constant which defines the electrical activity of defects expressed in cm2/~sec and to is background generation lifetime expressed in ~sec (24). The constant k had a value of 2 • 10 -6 in Fig.…”
Section: Suppression Of Defect Formation By ~Aser Damagementioning
confidence: 99%
“…However, it has been reported that OISF-related degradation in electrical properties was observed only when the stacking faults were decorated with impurities (20,21). It has also been reported that metallic impurities such as Fe, Cr, Ni, Cu, and Au could often be introduced as contaminants during epitaxial processing (22,23).…”
Section: Table II Minority Carrier Generation Lifetimes In Epitaxial ...mentioning
confidence: 99%